Menerapkan Algoritma Neural Network Pada Chatbot Mengenai Pariwisata Di Provinsi Bangka Belitung - Mahendra, Ristian; Kamayani, Mia (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Bangka Belitung Province, precisely in South Bangka regency, is one of the areas that have the potential to be visited by tourists. However, not all attractions are known by tourists due to lack of information. From these problems, researchers tried to develop a chatbot system. Chatbot is a program that conducts conversations between humans and machines using human language. This chatbot system aims to help tourists do questions and answers automatically to find information about tourist attractions in South Bangka.  The chatbot system applies a model with a natural language processing approach and neural network algorithms. This study aims to create a chatbot model that can provide information with good accuracy about paratourism in Bangka Belitung Province, especially South Bangka district. The data used in this study were the results of interviews and filling out questionnaires to the community. Then the data obtained is stored and converted into JSON format consisting of 173 tags, 618 patterns, and 187 responses. Then preprocessing the data was carried out by taking 25 random test questions. The results of the chatbot system accuracy test got an accuracy score of 92% from 25 questions asked randomly by getting an error value of 8%. From the results of accuracy testing, the chatbot system gets a response by looking at the appropriate questions asked by users based on tags, so that they can get the right answer.